Pengaruh Penggunaan Audio Visual sebagai Media Pembelajaran terhadap Pemahaman Konsep IPA Materi Struktur Lapisan Bumi Siswa Kelas V Sekolah Dasar - Hilda Lestari; Kayla Wahyuningtyas; Lilis Nurul Aini; Yadi Heryadi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Understanding scientific concepts in elementary school, particularly the topic of Earth's layers, remains a challenge due to its abstract nature. Low student interest and difficulty in visualizing geospheric structures highlight the need for more contextual and engaging learning media. This study aims to examine the effect of using audiovisual media on fifth-grade students' understanding of science concepts. A quantitative approach with a quasi-experimental design was employed, involving two groups: an experimental class using audiovisual media and a control class using conventional methods. The analysis revealed a significant difference in concept comprehension between the two groups. Students exposed to audiovisual media demonstrated greater improvement in understanding compared to those taught through traditional methods. These findings suggest that audiovisual media effectively support students in grasping abstract concepts through engaging visual and auditory presentations. The study implies that integrating interactive learning media is essential to enhance the quality of science education in elementary schools.